Da violência obstétrica à humanização do parto: uma necessária evolução sob o olhar jurídico - Silva, Amanda Rosito da (Universidade do Vale do Rio dos Sinos, 2021)
This paperwork os course conclusion brings, as it’s central theme, the juridical-legal treatment of obstetric violence in the Brazilian legal system and the framework of humanized childbirth as a fundamental right. The objective os this work is to demonstrate the need for the violence obstetrics to be recognized by law operators and, specifically, to conceptualize this kind of violence, examining how obstetric violence is treated in the national legal system, and provide subsidies for a better framework, as well as to treat humanizing birth as a fundamental right, wich must be guaranteed by the State, and demonstrating how juridical science can contribute to the humanization of childbirth and the prevention of obstetric violence. The method of data collection used was that of bibliographic research, carried out in na explanatory manner and with na eminently qualitative approach
Keywords: Violência obstétrica; Violência institucional e de gênero; Violação de Direitos Humanos; Responsabilidade Civil; Responsabilidade Penal; Parto humanizado; Obstetric violence; Institucional and gender violence; Violation of human rights; Civil responsability; Criminal responsability; Humanized birth